1996
DOI: 10.1038/nm0796-811
|View full text |Cite
|
Sign up to set email alerts
|

Specific P53 mutations are associated with de novo resistance to doxorubicin in breast cancer patients

Abstract: The mechanisms causing resistance to chemotherapeutic drugs in cancer patients are poorly understood. Recent evidence suggests that different forms of chemotherapy may exert their cytotoxic effects by inducing apoptosis. The tumor suppressor gene P53 has a pivotal role inducing apoptosis in response to cellular damage. In vitro investigations have shown intact p53 to play a critical role executing cell death in response to treatment with cytotoxic drugs like 5-fluorouracil, etoposide and doxorubicin. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
406
3
9

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(433 citation statements)
references
References 9 publications
15
406
3
9
Order By: Relevance
“…1, mutation (demonstrated at the DNA level) has been associated with poor prognosis on 3-6 years follow-up (Andersen et al, 1993; Thorlacius et al, 1993;Silvestrini et al, 1996). Furthermore, the precise location of the mutation may add further information of prognostic value (Bergh et al, 1995;Borressen et al, 1995) and predict response to chemotherapy (Elledge et al, 1995;Aas et al, 1996). p53 protein expression has been identified as a predictor of disease recurrence (Iwaya et al, 1991;Barnes et al, 1993;Friedrichs et al, 1993;Marks et al, 1994), even for patients without nodal involvement at the time of diagnosis (Allred et al, 1993;Barnes et al, 1993;Silvestrini et al, 1993;MacGrogan et al, 1995) and for poor survival (Isola et al, 1992;Allred et al, 1993;Silvestrini et al, 1993;Received 12 March 1997 Revised 25 July 1997 Accepted 21 August 1997 Correspondence to: AM Thompson Elledge and Borg et al, 1995;MacGrogan et al, 1995;Silvestrini et al, 1996).…”
mentioning
confidence: 99%
“…1, mutation (demonstrated at the DNA level) has been associated with poor prognosis on 3-6 years follow-up (Andersen et al, 1993; Thorlacius et al, 1993;Silvestrini et al, 1996). Furthermore, the precise location of the mutation may add further information of prognostic value (Bergh et al, 1995;Borressen et al, 1995) and predict response to chemotherapy (Elledge et al, 1995;Aas et al, 1996). p53 protein expression has been identified as a predictor of disease recurrence (Iwaya et al, 1991;Barnes et al, 1993;Friedrichs et al, 1993;Marks et al, 1994), even for patients without nodal involvement at the time of diagnosis (Allred et al, 1993;Barnes et al, 1993;Silvestrini et al, 1993;MacGrogan et al, 1995) and for poor survival (Isola et al, 1992;Allred et al, 1993;Silvestrini et al, 1993;Received 12 March 1997 Revised 25 July 1997 Accepted 21 August 1997 Correspondence to: AM Thompson Elledge and Borg et al, 1995;MacGrogan et al, 1995;Silvestrini et al, 1996).…”
mentioning
confidence: 99%
“…We also checked the expression of bcl-2 family proteins, regulators of drug-induced apoptosis, and found a mild up-regulation in cl-1 and remarkable up-regulation in cl-2 and cl-3 in Bcl-2 protein expression without a significant alteration in other bcl-2 family protein expressions ( Figure 6C). We also examined the expression of p53, which reportedly renders cells drug-sensitive (Aas et al, 1996 andJu et al, 1998), and a complicated result was obtained; cl-1 with a similar p53 expression as in parental cells; cl-2 with a significantly upregulated p53 expression; cl-3 with almost loss of p53 expression ( Figure 6C). To know the activity of p53, we examined the expression levels of p21, a downstream target of p53.…”
Section: Expressions Of Drug-resistance-associated Genes and A Differmentioning
confidence: 97%
“…Although studies have revealed its complicated mechanisms including enhancement in drug export by ATP-binding cassette transporter proteins (reviewed by Ross, 2000), activated drug detoxification by glutathione S-transferase (reviewed by Zhang et al, 1998), reduction in cell death commitment by loss or mutation of p53 (Aas et al, 1996 andJu et al, 1998), topoisomerase II down-regulation Yun et al, 1995) and apoptosis inhibition by over-expression of Bcl-2 family proteins (reviewed by Reed, 1997), triggering events that induce multi-drug resistance are not completely understood. It has been shown that the hypo-nutritive conditions promote a transient multi-drug resistance in solid tumours.…”
mentioning
confidence: 99%
“…Owing to the differing drug regimens and tumour subtypes tested, the analysis of TP53 mutations (and p53 protein expression) and anthracycline response has given conflicting results (Bidard et al, 2008). Although some reports suggest that TP53 mutations confer resistance to anthracyclines (Aas et al, 1996;Rahko et al, 2003), others have shown mutations to increase sensitivity (Bertheau et al, 2002(Bertheau et al, , 2009. Similarly, BRCA1 has multiple roles in breast cancer including DNA damage repair, transcriptional regulation, and regulation of cell cycle checkpoints.…”
Section: Other Potential or Emerging Markersmentioning
confidence: 99%